HEALTH AND REPRODUCTIVE RIGHT (International Journal of Food and Nutritional Sciences, 2022)
This paper delves into the right of health and reproduction under Article 21 of the Indian Constitution. The Importance of spreading awareness so that various kind of diseases can be prevented. The state is under the obligation to ensure the people about these rights as in rights specially for women regarding their choices of reproduction. This paper reflects the problems which are caused if these rights are denied and prescribes various policys for self determination.